Safety and Efficacy of 5 Years of Treatment With Recombinant Human Parathyroid Hormone in Adults With Hypoparathyroidism - Mannstadt, Michael (J Clin Endocrinol Metab, 2019)
CONTEXT: Conventional hypoparathyroidism treatment with oral calcium and active vitamin D is aimed at correcting hypocalcemia but does not address other physiologic defects caused by PTH deficiency. OBJECTIVE: To evaluate long-term safety and tolerability of recombinant human PTH (1-84) [rhPTH(1-84)]. DESIGN: Open-label extension study; 5-year interim analysis. SETTING: 12 US centers. PATIENTS: Adults (N = 49) with chronic hypoparathyroidism. INTERVENTION(S): rhPTH(1-84) 25 or 50 µg/d initially, with 25-µg adjustments permitted to a 100 µg/d maximum. MAIN OUTCOME MEASURE(S): Safety parameters; composite efficacy outcome was the proportion of patients with ≥50% reduction in oral calcium (or ≤500 mg/d) and calcitriol (or ≤0.25 µg/d) doses, and albumin-corrected serum calcium normalized or maintained compared with baseline, not exceeding upper limit of normal. RESULTS: Forty patients completed 60 months of treatment. Mean albumin-corrected serum calcium levels remained between 8.2 and 8.7 mg/dL. Between baseline and month 60, levels ± SD of urinary calcium, serum phosphorus, and calcium-phosphorus product decreased by 101.2 ± 236.24 mg/24 hours, 1.0 ± 0.78 mg/dL, and 8.5 ± 8.29 mg(2)/dL(2), respectively. Serum creatinine level and estimated glomerular filtration rate were unchanged. Treatment-emergent adverse events (AEs) were reported in 48 patients (98.0%; hypocalcemia, 36.7%; muscle spasms, 32.7%; paresthesia, 30.6%; sinusitis, 30.6%; nausea, 30.6%) and serious AEs in 13 (26.5%). At month 60, 28 patients (70.0%) achieved the composite efficacy outcome. Bone turnover markers increased, peaked at ∼12 months, and then declined to values that remained above baseline. CONCLUSION: Treatment with rhPTH(1-84) for 5 years demonstrated a safety profile consistent with previous studies and improved key biochemical parameters.